The DESIGN AND DEVELOPMENT OF COMBAT ROBOT SYSTEM ON THE CIA VERSION N2MR3 USING THE INTERNET OF THINGS (IOT) BASED RASPBERRY PI 4.0 - Penu, Melkianus; Gunawan, Petrus; Huda, Muhamat Maariful (Pustaka Poltekad, 2021)
Abstract - Along with the rapid development of science and technology, including robot technology. It can lighten and help the work done by humans. In the military world, the role of robots is indispensable both in peace and in war. This research was carried out using a pure experimental method on the Design of a Propulsion System for Combat Robots using the Internet of Things (IoT) Based on Raspberry 4.0. The working principle of this combat robot is based on data sent using MiFi (Tx) which will then be processed using Raspberry 4.0 and transmitted to MiFi (Rx) via the Internet of Things (IoT). Furthermore, the data received will be processed so that the driving system will produce driving force using a differential drive system, the difference in rotation of the driving motor is regulated by the microprocessor to the MY 1061 speed control, the pulse signal sent by the Raspberry Pi will regulate the amount of current sent to the DC motor so that the motor can turn left and right.